Teacher Professional Development and Teaching Quality - Tapadia, Swapnaja (Journal of Educational Research and Policies, 2024)
For pupils to learn effectively, the quality of the instruction is critical. To become even more skilled educators, teachers must continue to learn. We refer to this procedure as "professional development. " In this study, we examined the relationship between teaching quality and professional development for teachers. We discovered that children typically learn more when teachers receive quality training and assistance to enhance their teaching abilities. Additionally, we discovered that instructors are more likely to employ successful teaching techniques in their classrooms when they feel encouraged and confident in their ability to improve as professionals. Students find learning to be more engaging and enjoyable as a result. Our findings demonstrate the high value of funding teacher professional development. Authors of paper have focussed on both elements to improve quality of teaching.